Electrical engineering fundamentals - Rauf, S. Bobby, 1956- (Boca Raton, FL : CRC Press, 2020)
"In this book, the study of electrical engineering concepts, principles and analysis techniques is made relatively easy for the reader by inclusion of most of the reference data, in form of excerpts from different parts of the book, within the discussion of each case study, exercise and self-assessment problem solutions. This is in an effort to facilitate quick study and comprehension of the material without repetitive search for reference data in other parts of the book"--
OCLC-licensed vendor bibliographic record.
Keywords: Electrical engineering; TECHNOLOGY / Electricity